Genetic Diversity Analysis and F2 Population Development for Breeding of Long Juvenile Trait in Soybean - Tasma, I Made; Yani, N. P. Mega Gena; Purwaningdyah, Rosliana; Satyawan, Dani; Nugroho, Kristianto; Lestari, Puji; Trijatmiko, Kurniawan R.; Mastur, Mastur (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2018)
Genetic diversity analysis using molecular markers is an important step for selecting appropriate parents in a soybean breeding program. The aims of this study were to (1) analyze genetic diversity of 29 soybean genotypes assessed with 27 SSR markers for selecting appropriate parents and (2) develop F2 populations to be used for breeding long juvenile (LJ) trait in soybean tobe cultivated in short photoperiod condition. The soybean genotypes used consisted of 11 Indonesian soybean genotypes and 18 genotypes introduced from the USA. F2 populations were developed by crossing Grobogan with three introduced genotypes carrying LJ character. The PIC values of the 27 SSR markers ranged from 0.87 to 0.96. Cluster analysis resulted in three mainclusters at coefficient similarity of 0.76. The five LJ introduced accessions and the nine Indonesian genotypes showed high genetic distances and are useful as parent pairs for developing breeding populations. The F1 progeny phenotypicperformances of the cross far exceeded the performaces of both parents. Three F2 populations were developed by crossing the distantly related soybean genotypes. The F2 populations were verified by using SSR markers and it was found that they segregated in a 1:2:1 ratio confirming the segregation ratio of codominant SSR markers. The F2 populations should be useful for breeding LJ characters to improve soybean productivity in low latitude tropical countries such as Indonesia, which has day length of approximately 12 h all year round.